2006
DOI: 10.1080/14649370500463182
|View full text |Cite
|
Sign up to set email alerts
|

Conjuring the tropical spectres: heavy metal, cultural politics in Singapore and Malaysia

Abstract: The evolution of moral panics is dependent on the particular social context and the ability of certain issues to trigger concern within society. In this paper, the authors have employed a cross-comparative study of the heavy metal music subcultures in Singapore and Malaysia to understand the differences in the issues that generate such panics based on the sociopolitical context of each country and its current concerns. Although the youth involved in both cases are marginalised male Malays, the framing of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 4 publications
0
8
0
1
Order By: Relevance
“…From these initial contacts, I developed a snow-ball sample aided by the local BM scene member's suggestions of other individuals they considered as 'authentic'. Given the background of BM-related moral panics and consequent BM crackdowns in Malaysia in the early 2000s (Azmyl Yusof 2009;Liew and Fu 2006), the help of a gatekeeper was crucial to my access to the research's settings, because members of Malaysian Borneo's BM scene are wary of revealing their subcultural affiliation and musical tastes to strangers and newcomers. When they understood I was European, some responded enthusiastically about the fact a researcher from Europe was interested in their scene, while others maintained a certain level of scepticism and distance until our first meeting.…”
Section: Methods: Entering Malaysian Borneo's Bm Scenementioning
confidence: 99%
See 2 more Smart Citations
“…From these initial contacts, I developed a snow-ball sample aided by the local BM scene member's suggestions of other individuals they considered as 'authentic'. Given the background of BM-related moral panics and consequent BM crackdowns in Malaysia in the early 2000s (Azmyl Yusof 2009;Liew and Fu 2006), the help of a gatekeeper was crucial to my access to the research's settings, because members of Malaysian Borneo's BM scene are wary of revealing their subcultural affiliation and musical tastes to strangers and newcomers. When they understood I was European, some responded enthusiastically about the fact a researcher from Europe was interested in their scene, while others maintained a certain level of scepticism and distance until our first meeting.…”
Section: Methods: Entering Malaysian Borneo's Bm Scenementioning
confidence: 99%
“…The situation escalated into a ban of BM music in the state of Negeri Sembilan, and the obligation for foreign rock bands to submit video recorded performances of their music for approval before being allowed to play in Malaysia. Furthermore, in the district of Kuala Muda in Kedah, the police raided shows and record shops and arrested or questioned around 700 youth during a five-day operation (Liew and Fu 2006). About 150 of them were forced to be treated with a herbal drug that, according to Kedah state's officer Fadzil Hanafi, 'stimulates the brain so that students can concentrate on their studies' (BBC 2001).…”
Section: Malaysia Against Bmmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholarly research has indicated that music is often deemed subversive by totalitarian regimes (Keller 2007), and metal music in particular may agitate totalitarian or conservative regimes, as indicated by moral panics and state-sponsored backlash in Malaysia (Liew and Fu 2006) and parts of the Arab world (Levine 2009). As noted above, metal music is oppositional and frequently critical of the cultural and political status quo of its nation of origin.…”
Section: Control Variablesmentioning
confidence: 99%
“…9 These stereotypes reflect a widely held view in the non-Malay community that Malay men lack the key cultural and biological attributes that would enable them to succeed in the modern Singaporean economy (Li 1998). In his study of youth in the army, Leong Choon Cheong notes that Chinese national servicemen describe Malay men as 'lazy, unintelligent, unhygienic, and aggressive' (cited in Rahim 1998: 57-8), while laziness and drug taking also emerge as common stereotypes of Malay male youth in contemporary studies of popular culture (see Liew and Fu 2006). There has been little scholarly attention, however, to the continued salience of these stereotypes and the complexities surrounding 'Malay identity' over the last three decades, particularly in the context of growing class diversity amongst Malays.…”
Section: Singaporean Firstmentioning
confidence: 99%